Examining the efficacy of hybrid learning in students' English grammar achievement - Chairil Anwar Korompot; Warsita Umyah (International Journal of Humanities and Innovation (IJHI), 2023)
Students' knowledge and acquisition of a second language is seen to improve with hybrid learning. Using offline and online activities is anticipated to produce greater results than conventional face-to-face activities. This study aims to compare the levels of learning achievement between conventional and hybrid learning strategies used in an English grammar class. 40 year -7 students, divided into two classes of 20 each, participated in the study as respondents. Pre-experimental research methods were used in this study, and the participants' pre- and post-test mean scores were compared. Multiple-choice questions were present on both the pre-test and post-test. The results demonstrated an improvement in both the pre-test (46.5) and post-test (46.5) means (71.00). Also, data from the statistical analysis revealed that Sig. (2-tailed) is 0.000, less than (0.05), indicating a significant mean difference in grammar learning achievement affected by hybrid media after being supplied to students compared to conventional learning. It is concluded that hybrid learning may raise student achievement, particularly in English grammar.